Giuseppe Ferrari. Un pensatore eterodosso del nostro Risorgimento - Panizza, Giulio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
This paper focuses on Giuseppe Ferrari and Risorgimento socialism. The topic is treated with reference to Verri’s and Beccaria’s Lombard Enlightenment and to the radical views of Saint- Simon and Proudhon, in the context of the indictment of the Italian national unification seen as monarchical conquest or “piemontesismo”. From a theoretical perspective, Ferrari stresses the link between Vico and Romagnosi, in the source of a “civil philosophy” and of a conception of progress based on the notions of perfectibility and civilization. It is the study of mind in society and history, or Cattaneo’s “social ideology”.